Kendaraan Utama dan Pendukung PKP-PK Sebagai Penunjang Keselamatan Penerbangan - Gede Rivananda Widya Putra; Mohamad Fathan Azka Fakhreza; Nawang Kalbuana (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Indonesia is an archipelagic country that needs transportation in order to run the economy. Air transportation is the safest transportation at the moment, because it applies very strict standard operating procedures (SOP) for its operations. One of the most important aspects of air transportation is how airport managers ensure flight safety, namely by the presence of PKP-PK units. This research aims to understand the relationship between the main and supporting PKP-PK vehicles as supporting aviation safety. By using the literature review method as a research method, using various sources from journals, articles and books as references both online and offline. The results of this literature review article are: 1) The main PKP-PK vehicles have an influence in supporting flight safety; 2) PKP-PK support vehicles have an influence in supporting flight safety. The main and supporting vehicles are crucial factors in determining the effectiveness of handling emergency situations at the airport. Continuous efforts to improve the quality and readiness of PKP-PK units are a very valuable investment in maintaining the reputation of aviation safety.